Optimization of Machine Parameters for Hulling Efficiency of Black Gram - Garg, Sanjeev Kumar; Agrawal, U S (Journal of Agricultural Engineering, 2005)
Experiments were conducted in continuous mode of operation to study the effects of machine parameters, namely outlet opening, roller speed, roller length, roller inclination and grain moisture content, on milling responses of black gram using Response Surface Methodology. The range of favourable operating parameters were found to be 9.51 - 12.65% (d.b.) moisture content, 480.50 - 266.81 mmÂ² outlet opening, 13.70 -14.10 m/s roller speed, 27.63 - 38.44 cm roller length and 2.60 - 4.24 degree roller inclination.